Development Of Selective Extraction For Cd(II), Cu(II) And Ni(II) Ions Using Dual Flat Sheet Supported Liquid Membrane System - Lee, Lai Yee (2021)
Wastewater produced from washing out the mixtures and massive discharge of used acids usually have large mass of diverse metallic ions. In electroplating industry, treating the wastewater with various metals is a complex process whereby unwanted metallic ions are often discarded and only metals with high commercial values are separated for recovery. In fact, most of the existing wastewater treatments are non-selective and some are limited for removal of single metal. Due to close similarities in chemistry, metallic ions usually coexist and compete with each other to be selectively separated. Therefore, multiple metal ions could be separated from industrial effluent. Supported liquid membrane (SLM) allows heavy metals separation with the advantages include simultaneous extraction and stripping in a single step, supported with polymer with minimal usage of extractants and low energy use. Dual Flat Sheet Supported Liquid Membrane (DFSSLM) applies two separated SLMs to selectively recover not just one but three types of metal ions at the end of the system. This research aims to study the efficiency of DFSSLM in selective extraction of Cd(II) and Cu(II) over Ni(II) ions from aqueous mixture and electroplating wastewater. The effects of feed pH and carrier concentration for selective extraction of Cd(II) and Cu(II) over Ni(II) were investigated. The effects of pH, carrier concentration and masking agent concentration for separation of Cd(II) over Cu(II) were optimized. Operating parameters for DFSSLM were selected based on screening experiments: Feed phase containing 100 mg/L of Cd(II), Cu(II) and Ni(II) with pHeq 4.6, first membrane soaked with 100 mM di(2-ethylhexyl) phosphoric acid and 50 mM tributyl phosphate in kerosene, second membrane soaked with 99.64 mM trioctylmethylammonium chloride and 50 mM tributyl phosphate in toluene, and 1 M sulfuric acid in Intermediate phase and 48.86 mM ethylenediaminetetraacetic acid in the Strip phase. After 48 hours of stirring at 500 rpm, 98.79% of Ni(II) were found in Feed, 91.32% of Cu(II) in Intermediate, and 91.04% of Cd(II) in Strip compartment of DFSSLM. Competitive transportation between Cd(II) and Cu(II) was justified with the flux changes and kinetic studies of Cd(II) and Cu(II). Treatment using DFSSLM yielded high output/input ratios for recovered Cd(II), Cu(II) and Ni(II). 89.09% of Cd(II) recovered in Strip, 90.87% of Cu(II) in Intermediate, 97.61% of Ni(II) remained in Feed and most of the other heavy metals were eliminated. This study concluded that DFSSLM is efficient for separation and recovery of Cd(II), Cu(II) and Ni(II) from complex mixture.